2015
DOI: 10.1007/s11357-015-9824-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of melatonin and α-lipoic acid in the induction of antioxidant defences in L6 rat skeletal muscle cells

Abstract: Aging is characterized by a progressive deterioration in physiological functions and metabolic processes. The loss of cells during aging in vital tissues and organs is related to several factors including oxidative stress and inflammation. Skeletal muscle degeneration is common in elderly people; in fact, this tissue is particularly vulnerable to oxidative stress since it requires large amounts of oxygen, and thus, oxidative damage is abundant and accumulates with increasing age. Melatonin (N-acetyl-5-methoxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
3
20
0
2
Order By: Relevance
“…Furthermore, in our study, we evaluated the effects of melatonin treatment on skeletal muscle cell atrophy induced by reserpine observing that melatonin causes a significant increment in muscle weight and in myotubes diameter compared with RIM experimental group and the animals treated with reserpine and then only with tap water. In addition previous studies reported that melatonin reduces skeletal muscle atrophy and oxidative stress [ 49 , 61 , 62 ]. In order to confirm the antioxidant, ant-inflammatory and protective roles of melatonin, we evaluated the skeletal muscle expression of endogenous antioxidant and of constitutive molecules and we found that melatonin modulates muscoloskletal ultrastructure, increases expression of SOD1, CAT, COX-1 and SIRT3 and decreaes NLRP3 compared with RIM experimental group and also with the groups treated reserpine and then only with tap water.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, in our study, we evaluated the effects of melatonin treatment on skeletal muscle cell atrophy induced by reserpine observing that melatonin causes a significant increment in muscle weight and in myotubes diameter compared with RIM experimental group and the animals treated with reserpine and then only with tap water. In addition previous studies reported that melatonin reduces skeletal muscle atrophy and oxidative stress [ 49 , 61 , 62 ]. In order to confirm the antioxidant, ant-inflammatory and protective roles of melatonin, we evaluated the skeletal muscle expression of endogenous antioxidant and of constitutive molecules and we found that melatonin modulates muscoloskletal ultrastructure, increases expression of SOD1, CAT, COX-1 and SIRT3 and decreaes NLRP3 compared with RIM experimental group and also with the groups treated reserpine and then only with tap water.…”
Section: Discussionmentioning
confidence: 98%
“…Remarkably, melatonin supplementation in NLRP3 KO mice was particularly beneficial to retard the onset of sarcopenia in gastrocnemius muscle in aged animals [91]. Interestingly, exogenous melatonin regulated insulin resistance, ameliorated mitochondrial function in rat muscles, and prevented chemically induced apoptosis and endoplasmic reticulum stress in different skeletal muscle cells in vitro [92][93][94][95][96][97].…”
Section: Melatonin Alleviates Skeletal Muscle Disorders In Vitro and mentioning
confidence: 99%
“…Notably, conditional ablation of the pancreatic clock causes diabetes mellitus (DM) due to impaired beta-cell function at the very latest stage of stimulus-secretion coupling. These results demonstrate a role of the beta-cell clock in coordinating insulin secretion with the sleep-wake cycle and reveal that ablation of the pancreatic clock can trigger the DM onset [4].…”
Section: Introductionmentioning
confidence: 62%
“…Oxidative stress plays a pivotal role in the development of diabetes complications, both microvascular and cardiovascular. Melatonin [4,12], a potent antioxidant agent, is essential for glucose homeostasis and regulation. It has been determined (Czuczejko J., Sielski Ł., 2019) that melatonin supplementation influenses oxidative stress parameters in elderly patients with noninsulin dependent diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%